A 15-Month-Old Boy With Respiratory Distress and Parapharyngeal Abscess: A Case Report - Behdad Gharib; Masoud Mohammadpour; Meisam Sharifzadeh; Fatemeh Mirashrafi; Bahareh Yaghmaie; Neda Pak; Mehrzad Mehdizadeh; Hamid Eshaghi; Mojtaba Gorji; Sara Memarian (Acta Medica Iranica, 2017)
Parapharyngeal abscess is a life-threatening disease. Upper respiratory tract infection is the main cause in children. We present a 15-month-old boy admitted to the emergency ward with the chief complaint of difficulty in breathing caused by parapharyngealabscess. His condition deteriorated gradually, and he transferred to the operation theater quickly for abscess drainage and because of the difficulty in orotracheal intubation; a tracheostomy was performed. His respiratory condition deteriorated 2 days after PICU admission, and the medical team noticed an unexplainable respiratory distress. A chest x ray obtained and showed a right side pneumothorax and subcutaneous emphysema around theneck area. The case presented here, had not been diagnosed at the first examination; however, there were enough clinical clues (such as respiratory distress, drooling, torticollis, bulging of theneck, previous viral respiratory infection, possible pharyngeal trauma). The story of this case reminds us the importance of the precise physical exam and history taking which could be life-saving.